The destruction of the Parthenon - Chryssopoulos, Christos; Jassogne, Pierre (Sens public)

(untitled) (Département des littératures de langue française, 2013)
The Greek novelist and essayist Christos Chryssopoulos was inspired by the surrealist poet Yorgos Makris magining, during World War II, the "total destruction of the classical monuments" starting with the most prestigious and symbolic of all, the Parthenon. He has built his novel The Destruction of the Parthenon upon this story, combining history with the contemporary nnd fiction with documentation. Since the economic, political and social crisis is ravaging the writer's country, his novel's impact seems to be notably amplified. The author's interview by the Belgian journalist Pierre Jassogne, in the midst of 2012's autumn, is based on such a point of view, asking him as well to cast his opinion about the role of the intellectuals in these times of crisis. The most recent book by Christos Chryssopoulos ({Une lampe entre les dents. Chronique athénienne}, released in February 2013) mingles a poetical meditation with fiction and a review of the present situation. Published by Actes Sud, those books have been translated by Anne-Laure Brisac.